Evaluación de la concentración mínima de inhibición de polifenoles como antimicrobianos para el crecimiento de Listeria monocytogenes - Torres Salvatierra, Brayan Fernando (2025)
This study was conducted using a completely randomized, two-factor, triplicate design to evaluate the antimicrobial activity of different concentrations of flavonoid-rich extracts from orange (Citrus sinensis), onion (Allium cepa), and tamarillo (Solanum betaceum) against the growth of Listeria monocytogenes in fruit juices. The peels of these fruits were dehydrated at controlled temperatures between 50 and 57 °C for eight hours and then ground into powder. The yields obtained after this process were 32% for orange, 13% for onion, and 14% for tamarillo. Flavonoid extraction was performed using the Soxhlet method with 70% ethanol for five hours, followed by concentration in a rotary evaporator. The extracted compounds were quantified by UV spectrophotometry and the Folin-Ciocalteu method. The results showed that orange extracts had the highest concentrations (300.75–372.60 mg quercetin equivalents per liter), followed by onion extracts (205.70–534.96 mg Q/L). Lower values were observed for tamarillo, possibly due to measurement errors or variability in the plant matrix. Soluble solids losses during the extraction process varied, reaching 5.27 g for orange. In terms of antimicrobial activity, orange extracts demonstrated greater efficacy as natural preservatives, inhibiting the growth of Listeria monocytogenes with minimum inhibitory concentrations between 300 µg/mL and 400 µg/mL